Challenges and choices for patient, carer and professional at the end of life : living with uncertainty - Proot, Catherine; Yorke, Michael (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Living with Uncertaintygives a broad perspective on the complexities and challenges of the practice of end-of-life care, as well as the perceived benefits and limitations of medical intervention. Drawn from research andclinical and pastoral experience, the book examines the feelings associated with the end of life, highlighting the demands that people are faced with and their consequences. It moves into the difficult area of people who feel defeated by their illness and can or want to live no longer, as well as the family, caregivers and professionals who surround them. These perspectives have been built upon around a hundred narratives of lived experience, combined with the wider clinical and practical range of voices. A topical post-script Lessons from Covid-19 captures the choices and challenges on apersonal, professional and systemic level which the pandemic acutely revealed with a multiplicity of examples. This will be essential reading for students and professionals in palliative and end-of-life care. Families and friends will also benefit from this book as they try to come to terms with the delicate but universal issues of death and dying.
Introduction; Part I: The dying person and their loved ones; Chapter 1: Attitudes to death and dying; Chapter 2: The end of life - people's experiences; Part II: Medicine and care at the end of Life; Chapter 3: Medical intervention, a life saver or a life changer?; Chapter 4: Euthanasia and assisted dying; Chapter 5: Person-centred care; 6: Conclusion; 7: Post-script: Lessons from Covid-19; Glossary
OCLC-licensed vendor bibliographic record.
Keywords: Terminal care; Palliative treatment; Terminally ill; PSYCHOLOGY / Mental Health